Progress on the Elucidation of the Antinociceptive Effect of Ginseng and Ginsenosides in Chronic Pain - Li, Mei-Xian; Wei, Qian-Qi; Lu, Huan-Jun (Frontiers in Pharmacology, 2022)
Ginseng (Panax ginseng C.A. Meyer) is a traditional Oriental herbal drug widely used in East Asia. Its main active ingredients are ginsenosides whose constituents are known to have various pharmacological activities such as anticancer, antinociception, and neuroprotection. The analgesic effects of ginsenosides, such as Rg1, Rg2, and Rb1, as well as compound K, are well known and the analgesic mechanism of action in inflammatory pain models is thought to be the down regulation of pro-inflammatory cytokine expression (TNF-α IL-1β, and IL-6). Several studies have also demonstrated that ginsenosides regulate neuropathic pain through the modulation of estrogen receptors. Recently, an increasing number of pathways have emerged in relation to the antinociceptive effect of ginseng and ginsenosides. Therefore, this review presents our current understanding of the effectiveness of ginseng in chronic pain and how its active constituents regulate nociceptive responses and their mechanisms of action.